Evaluation of actions, barriers, and facilitators to reducing dietary sodium in health care institutions. Issue 8 (30th September 2018) - Lacey, Michael; Chandra, Sharon; Tzianetas, Roula; Arcand, JoAnne
Abstract: Background: Globally, population‐wide sodium reduction strategies have been adopted and implemented to address the adverse health effects of excess dietary sodium. However, in Canada, minimal coordinated action by governments has occurred, including interventions aimed at food service operations in hospitals and long‐term care (LTC) centers. The objective of this study was to investigate actions, attitudes, barriers, and facilitators related to sodium reduction in these institutions. Methodology: A cross‐sectional survey was administered to food service administrators working in hospitals and LTC facilities in Ontario. Responses from key informants from 27 institutions, representing 9, 823 patient/resident beds were included. Results: Overall, 63.0% of institutions had an established sodium target (900–4, 000 mg/day). The reported sodium level on "regular" menus was 2, 845 ± 1, 025 mg/day. Sixty‐three percent believed it was important to reduce sodium on inpatient/resident menus. Top facilitators reported for sodium reduction included group purchasing organizations identifying lower sodium foods (85.2%), increased availability of pre‐packaged lower sodium products (77.8%), government prioritizing and providing support and resources (74.1%), and improved taste of lower sodium foods (74.1%). Only 37.0% believed that patient/resident satisfaction would decrease with sodium reduction. Sodium reduction practices were variable among food service operations. Conclusions: These data support the need for consistent and coordinated policies to facilitate sodium reduction in hospitals and long‐term care settings and for multi‐sectorial government, industry, and institutional support to ensure success.